Diel changes in bacteriochlorophyll a concentration suggest rapid bacterioplankton cycling in the Baltic Sea - Koblízek, Michal; Stoń-Egiert, Joanna; Sagan, Sławomir; Kolber, Zbigniew S (FEMS microbiology ecology, 2005)
Aerobic anoxygenic phototrophs were recently found to constitute a significant portion of the marine microbial community. These bacteria use bacteriochlorophyll-containing reaction centers to perform photoheterotrophic metabolism. A new instrument for routine measurements of both chlorophyll a and bacteriochlorophyll a was used for monitoring anoxygenic phototrophs in the Baltic Sea in late summer 2003. Bacteriochlorophyll a concentration ranged from 8 to 50 ngl(-1), with an average bacteriochlorophyll/chlorophyll ratio of 4.2 x 10(-3). Moreover, diel trends in bacteriochlorophyll a signals were observed, with a distinct decline occurring during daylight hours. Based on laboratory measurements this phenomenon was ascribed to the complete inhibition of bacteriochlorophyll synthesis by light, which, in combination with a concurrent turnover of the cells, resulted in a pigment decline. Following this explanation, we postulate that bacteriochlorophyll a can serve as a natural 'pulse-and-chase' marker, allowing estimation of the mortality rates of anoxygenic phototrophs from the rates of pigment decline. Based on this assumption, we suggest that the Baltic photoheterotrophic community was characterized by high turnover rates, in a range of 0.7-2 d(-1).
Keywords: Circadian Rhythm; plankton; Bacteriochlorophyll A; Fluorometry; Baltic States; Time Factors; cirkadiánní rytmus; oceány a moře; Bacteriological Techniques; aerobióza; Aerobiosis; bakteriologické techniky; fluorometrie; pobaltské republiky; fotosyntéza; Sphingomonadaceae; bakteriochlorofyl A; Plankton; mořská voda; zvířata; Seawater; Photosynthesis; časové faktory; Oceans and Seas; Animals